The Recurrent Mutation in PATL2 Inhibits Its Degradation Thus Causing Female Infertility Characterized by Oocyte Maturation Defect Through Regulation of the Mos-MAPK Pathway - Cao, Qiqi; Zhao, Chun; Wang, Congjing; Cai, Lingbo; Xia, Meng; Zhang, Xiaolan; Han, Jian; Xu, Yangyang; Zhang, Junqiang; Ling, Xiufeng; Ma, Xiang; Huo, Ran (Frontiers in Cell and Developmental Biology, 2021)
PAT1 homolog 2 (PATL2), encoding an RNA-binding protein, is a repressor involved in the translational regulation of maternal mRNAs during oocyte maturation. Previous studies have reported mutations in PATL2 those led to female infertility with oocyte maturation arrest; however, the mechanisms by which mutations affected meiotic maturation remained unclear. Here, we identified several novel and recurrent mutations of PATL2 in patients with similar phenotype, and chose the missense mutation c.649A>G p.Tyr217Asn in PATL2 (PATL2Y217N) as a typical to investigate the underlying mechanism. We confirmed that this mutation disturbed oocyte maturation and observed morphological defects of large polar body, symmetrical division and abnormal spindle after microinjection of corresponding mutated mRNA. We further evaluated the effect of the PATL2Y217N mutation in 293T cells, and found this mutation decreased the ubiquitination level and degradation of PATL2. Then, abnormally increased PATL2 bound mRNAs of Mos, an upstream activator of mitogen activated protein kinase (MAPK), to regulate its translational activity and subsequently impaired MAPK signaling pathway and impeded oocyte meiotic maturation. These results dissented from the previous view that PATL2 mutations reduced their expression and highlight the role of PATL2 in translational regulation of Mos and its association with MAPK signaling pathway during oocyte maturation.